Trauma trajectories: a longitudinal study of asylum seekers diagnosed with PTSD in Greece - Womersley, Gail (My University, 2017)
The literature reports significantly high levels of PTSD among asylum seekers, yet the diagnosis is criticized for necessarily requiring one past ‘traumatic’ event – thereby neglecting post-migration factors significantly influencing mental health (Abbott, 2016; Bäärnhielm, 2016; Hall & Olff, 2016; Maercker & Hecker, 2016). To explore the life trajectories of asylum seekers, and more particularly temporal dimensions of experiences of trauma, we present the results of a yearlong qualitative research intervention in Athens. This project includes a longitudinal follow up of 10 asylum seekers, identified as victims of torture and diagnosed with PTSD, as well as 60 interviews with their treating medical professionals and community representatives. We explore the dynamic processes inherent to their life trajectories – focusing on the continual development and change in psychological symptoms of trauma; ever-changing political, cultural and social systems; and how these individuals cope with situations of psychological rupture including experiences of migration (Kadianaki & Zittoun, 2014). Abbott, A. (2016). The troubled minds of migrants. Nature, 538, 158-161. Bäärnhielm, S. (2016). Refugees' mental health-a call for a public health approach with focus on resilience and cultural sensitivity. European Journal of Public Health. doi:10.1093/eurpub/ckw055 Hall, B. J., & Olff, M. (2016). Global mental health: Trauma and adversity among populations in transition. European journal of psychotraumatology, 7. Kadianaki, I., & Zittoun, T. (2014). Catalysts and regulators of psychological change in the context of immigration ruptures The Catalyzing Mind (pp. 191-207): Springer. Maercker, A., & Hecker, T. (2016). Broadening perspectives on trauma and recovery: A socio-interpersonal view of PTSD. European journal of psychotraumatology, 7.
, 15th SPS SGP SSP Conference, Lausanne, Switzerland